Hypothesis on etiopathogenesis, congenital or acquired, of an imperforate distal ureter: a case report. (December 2015) - Bagnara, Vincenzo; Castorina, S.; Nappo, S.; Privitera, G.; Luca, T.; Caione, P.
Abstract Introduction Ureteral atresia is a rare disease usually associated with a non-functioning kidney. Its association with other urinary anomalies is rare. Case presentation In this study we discuss the possibility of congenital or acquired etiology of a right imperforate distal ureter. Here we report the case of 11-month-old white boy with a right ureteropelvic junction obstruction. He underwent a right pyeloplasty when he was 11-months old, and 3 weeks after surgery a cystoscopy was performed. Two months after the first operation, he underwent a right ureteral meatoplasty and a new pyeloplasty. Conclusions To the best of our knowledge, few cases of imperforate distal ureter have been described in the literature. The suspicion of a non-patent terminal ureter, occurring during upper urinary tract surgery, must be intraoperatively clarified to preserve the renal function and to avoid more complex surgical approaches.